Ensuring Environmental Integrity under Article 6 Mechanisms - World Bank (World Bank, Washington, DC, 2021)
Ensuring environmental integrity is recognized as an important goal under Article 6. This paper examines factors that affect environmental integrity under Article 6 of the Paris Agreement, and identifies practical approaches for implementing the concept based on lessons learned from the World Bank’s pilot activities and feedback from stakeholders in pilot countries. The starting point is the commonly accepted definition that environmental integrity is ensured as long as global greenhouse gas (GHG) emissions do not increase as a result of transfers of mitigation outcomes (MOs) (when compared to the scenario where such transfers did not take place). Under the Kyoto protocol, not all countries had mitigation obligations. In contrast, the Paris Agreement requires all countries to voluntarily adopt individual targets, articulated in their nationally determined contribution (NDC). This effectively introduces a national commitment or emissions cap for the entire economy or for the sectors covered by the NDC. This means that the transfer of MOs will affect the host country’s ability to achieve its own NDC if decisions related to such transfers do not take into account the need for corresponding adjustments and the opportunity cost of making such adjustments. In this context, ensuring environmental integrity - transferring MOs without affecting the country’s ability to meet its NDC and ensuring that such transfers do not lead to an increase in global GHG emissions - requires the assessment of two aspects: (1) stringency of NDC compared to business as usual (BAU): whether the country’s emissions cap or NDC is stringent enough and its targeted GHG emissions are not higher than what will be expected under business as usual (BAU) conditions; and (2) unit quality: whether the volume of transferred MOs generated from a mitigation activity is accurately calculated by setting a stringent or conservative baseline.